Information needs of financial market professionals in the big data and social media era. The empirical evidence from Poland - Andrzej Cwynar; Wiktor Cwynar; Robert Pater; Piotr Kaźmierkiewicz (e-Finanse: Financial Internet Quarterly, 2017)
To meet general objectives of the article, i.e. to check the extent to which the information needs of financial market institutions are satisfied, and to learn about whether there is a transition in this realm triggered by the advent of social media and big data, we surveyed a sample of 415 financial market professionals working in Poland. We also used logit regression models, through which we processed the survey results, to identify which factors are responsible for meeting the needs. We showed that although the information needs of financial market professionals are met to a large degree, still some potential for improvement remains in this regard. We found also that respondent-specific traits are insignificant in explaining the degree of satisfaction with data and information that is used by financial market professionals. Out of firm-specific characteristic and, the value of assets under the institution's management turned out to be the key factors explaining the distribution of responses concerning satisfaction.
Keywords: G14; G23; G24; 330; financial market professionals; information needs; big data; social media; financial institutions